A Narrative Analysis of Stories Told about Engineering in the Public Discourse: Implications for Equity and Inclusion in Engineering - Nicola W. Sochacka (Studies in Engineering Education, 2021)
Background: Stories are a natural and powerful way for humans to make sense of complex situations. Prior research suggests that when people are faced with complex problems, like underrepresentation in engineering, they construct and defer to stories, sometimes even in the face of contradicting evidence, as a basis for decision making and action. Purpose/Hypothesis: We examined the public discourse to identify stories about underrepresentation in engineering, and about engineering more broadly, that inform and underwrite efforts to address the dual problem of a general lack of interest in engineering careers and a lack of diversity in engineering graduates and professionals. Design/Method: Drawing on the theory of framing and concepts from narrative policy analysis (NPA), we qualitatively analyzed one year of online news articles (from August 2011 to August 2012) sourced from a news briefing service for engineering educators. Results: We describe five dominant stories about engineering that define the field in terms of math and science, building things, the need for societal appreciation, diversity-driven innovation, and hard-earned career rewards, respectively. These stories share a common premise—that a chronic shortage of engineers threatens the economic growth and international competitiveness of the United States. Each story includes explanations for perceived low levels of interest in the field and recommendations to address this problem. We note that increasing the participation of groups from diverse ethnic backgrounds was not a prominent theme in the discourse we analyzed compared to, for example, attracting more women or increasing the overall number of young people who are interested in engineering careers. Consistent with NPA, we also describe a nonstory that critiques the premise of the dominant stories. Conclusions: We discuss how the dominant stories reflect a particular set of values and practices, centered on competition, economic gain, and the design of technological artifacts that, in turn, shape efforts to attract, educate, and retain students. We further discuss how alternative narratives may open up new opportunities for systemic, cultural change in engineering education with important implications for diversifying the field.